1997
DOI: 10.1093/humrep/12.3.474
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal normality of unfertilized oocytes from patients with polycystic ovarian syndrome

Abstract: The present study was designed to compare the cycle characteristics of in-vitro fertilization (IVF) and the chromosomal normality of oocytes in patients with polycystic ovarian syndrome (PCOS) with those of patients with tubal factor infertility. In all, 28 cycles of 24 PCOS patients and 55 cycles of 31 patients with tubal factor infertility (control) were investigated. Although a significantly greater number of oocytes were retrieved from PCOS patients (mean +/- SD: 15.6 +/- 6.4 versus 9.0 +/- 4.0, PCOS versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 8 publications
2
32
0
5
Order By: Relevance
“…Some have suggested a decreased fertilization rate in PCOS patients but this reduced rate does not appear to be attributable to cytogenetic immaturity or chromosomal aberrations [9]. In addition there is little evidence in the literature that PCOS results in lower than normal pregnancy or live birth rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested a decreased fertilization rate in PCOS patients but this reduced rate does not appear to be attributable to cytogenetic immaturity or chromosomal aberrations [9]. In addition there is little evidence in the literature that PCOS results in lower than normal pregnancy or live birth rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization rates in women with PCOS are also reported to be lower [49,50]. Despite the above studies; studies have found no difference in aneuploidy rates between PCOS and control oocytes [49] and pregnancy rates do not always differ [49,50].…”
Section: Oocyte Maturation and Fertilizationmentioning
confidence: 93%
“…The utilization of low doses of gonadotropin plus the recovery of great numbers of MII oocytes might have reduced the impact of high incidence of degeneratedand immature oocytesrateson pregnancy outcomes in PCOS and PCOM patients. Moreover, the lack of association between PCOS and embryonic aneuploidy [36], and the similar chromosomal normality of unfertilized oocytes from patients with or without PCSO [37], might have also contributed to the high pregnancy outcomes in PCSO or PCOM patients observed in this study.…”
Section: Discussionmentioning
confidence: 80%